The first-largest shareholder and the attractiveness of investing in Polish dividend companies - Pieloch-Babiarz, Aleksandra (Public Policy and Accounting, 2021)
The purpose of this article is to examine the attractiveness of investing in shares of listed companies that regularly pay out dividends depending on the type of the first-largest shareholder. In order to achieve the aim of the paper, two following research questions we formulated: 1) in which companies, broken down by type of the first-largest shareholder, is the highest dividend payment observed? 2) considering the main shareholder, owning shares of which dividend companies is most beneficial for a stock market investor? Furthermore, the research hypothesis is: when investing in dividend, the most attractive investments are those companies in which the most shares are held by institutional investors and the State Treasury. The research was conducted on non-financial companies listed on the Warsaw Stock Exchange in the years 2005-2019 that regularly paid out dividends. The main research method was the classical technique for order of preference by similarity to ideal solution (i.e., TOPSIS) in which stimulants and destimulants were selected in a way which enables to assess the investment attractiveness from the point of view of a long-term stock market investor interested in dividend. Moreover, the Pearson correlation matrix and descriptive statistics were used. In order to conduct the computation we used the statistical software Statistica 13.5 and Excel. The research revealed that the highest dividends were paid out by these companies in which the first-largest shareholder was the institutional investor. In addition, our calculations based on a synthetic indicator showed that the most attractive investments (in terms of stock market investor interested in so called ‘dividend investing’) were shares of these companies in which the main shareholder was an institutional investor, individual investor and legal person. In all these types of companies, the average value of dividend payout ratio was higher than in the entire research group. The fourth position in terms of investment attractiveness was occupied by the companies in which managers held the most shares (these companies paid out the lowest dividends in the entire research group). The last place in the ranking was taken by the companies in which the State Treasury was the main shareholder (these companies, despite the payment of high dividends, turned out not to be attractive investment due to their financial condition, and in particular, very high debt).